The Effect of Ease of Use on Purchase Decisions through Buying Interest as an Intervening Variable - Prabowo, Ibnu Tri (Lentera Ilmu Nusantara, 2024)
This study aims to test the ease of use for purchase decisions through purchase intent as an intervention. In this study , it was analyzed using a statistical approach and the SEM PLS system model version 4. PLS analysis will be used to determine the best model in the calculation of the Buying Interest index using shopee. The method used in collecting data is the probability sampling method. Data was collected by distributing questionnaires to UPB students for the 2023-2024 batch in the form of a google form. To analyze the data, the PLS-SEM method was used with the help of SMARTPLS-4 software. PLS analysis has seven stages, namely: (1) development of theoretical models, (2) development of path diagrams, (3) conversion of path diagrams to structural equations, (4) selection of input matrices and estimation types, (5) identification of models, (6) assessment of goodness of fit criteria, (7) interpretation of results. The findings of the structural model have three hypotheses that are declared supported. The results of the study prove that there is a positive influence of ease of use on buying interest, there is a positive influence of buying interest on purchase decisions and there is a positive influence of ease of use on purchase decisions through purchase intention as mediation.